PEMBENTUKAN APARATUR YANG BERSIH DAN BERWIBAWA DENGAN PEMBERIAN SANKSI ADMINISTRASI DISIPLIN TERHADAP PEGAWAI NEGERI SIPIL (Faculty of Law, University of Palembang, 2022)
One indication of the low quality of Civil Servants is the existence of disciplinary violations that are mostly carried out by Civil Servants. The development that is being actively carried out in Indonesia often encounters many obstacles and quite complex problems. The problem in this research is the formation of a clean and authoritative apparatus by giving disciplinary administrative sanctions to Civil Servants and the impact of giving administrative sanctions to the discipline of Civil Servants. The approach method that will be used in this research is a normative legal research approach. Normative legal research is an approach method used to determine the legal norms contained in statutory regulations. The results of this study are ASN who are aware of their responsibilities are those who obey their obligations and stay away from all prohibitions in their responsibilities as ASN to fulfill good ASN character. With the aim of educating and fostering the state civil apparatus, those who violate the obligations and prohibitions will be subject to disciplinary punishment. The administration of administrative sanctions against the discipline of Civil Servants at the State Administrative Court has an impact on the judges and the Civil Servants concerned and others where they do not repeat such disciplinary actions.